2009
DOI: 10.1021/np800797v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Costaria costata Fucoidan on Expression of Matrix Metalloproteinase-1 Promoter, mRNA, and Protein

Abstract: Fucoidans are sulfated fucosylated polymers from brown algae cell walls. We assessed the inhibitory effects of Costaria costata fucoidan on UVB-induced MMP-1 promoter, mRNA, and protein expression in vitro using the immortalized human keratinocyte (HaCaT) cell line. Pretreatment with fucoidan significantly inhibited MMP-1 protein expression compared to UVB irradiation alone. Fucoidan significantly reduced MMP-1 mRNA expression and inhibited UVB-induced MMP-1 promoter activity by 37.3%, 53.3%, and 58.5% at 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…They have a heparin-like anticoagulant activity, inhibit selectin function, inhibit viral entry to cells, and appear to be immunomodulatory. Fucoidans from different species have been shown to inhibit Ultra-violet (UV)-induced matrix metalloprotease (MMP) expression in vitro [2][3][4]. Senni showed that fucoidans are extensive inhibitors of matrix metalloproteases, while fucoidan (or fucoidan-containing) extracts from Fucus vesiculosus and Ascophyllum nodosum have been shown to inhibit elastase [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…They have a heparin-like anticoagulant activity, inhibit selectin function, inhibit viral entry to cells, and appear to be immunomodulatory. Fucoidans from different species have been shown to inhibit Ultra-violet (UV)-induced matrix metalloprotease (MMP) expression in vitro [2][3][4]. Senni showed that fucoidans are extensive inhibitors of matrix metalloproteases, while fucoidan (or fucoidan-containing) extracts from Fucus vesiculosus and Ascophyllum nodosum have been shown to inhibit elastase [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Here, LMF treatment down-regulated the gene expression of MMP-1, MMP-9 and MMP-13. Previous studies have shown that native fucoidans modulate MMP-1 expression in human fibroblasts [14,15,16]. Furthermore, l -fucose and fucose-rich polysaccharides have a direct relationship with increased synthesis of elastin and collagen by down-regulating MMPs, particularly MMP-2 and MMP-9 [29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike native fucoidan with a high molecular-weight of approximately 20,000 kDa, low molecular-weight fucoidan (LMF)—less than 10 kDa—has shown more biological activities because of its high absorption and bioavailability [13]. However, a few studies have examined the anti-photoaging effect of fucoidans, which include three in vitro studies demonstrating the down-regulating effects on MMP-1 [14,15,16] and one in vivo study showing inhibitory effects on inflammation and MMP-1 expression following oral administration [17]. We previously showed that topical application of LMF has dermal wound healing effects with anti-inflammatory and antioxidant activities and modulates ECM rebuilding factors, such as transforming growth factor (TGF)-β1, fibroblast growth factor (FGF)-2, and MMPs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans extracted by these techniques exhibited in some cases a higher antioxidant activity than those extracted by conventional methods [53]. In addition to their antioxidant properties, fucoidans possess another biological activity relevant in the cosmetic field: they are able to prevent UVB-induced matrix metalloproteinase-1 (MMP-1) expression and suppress MMP-3 in vitro [39,55]. MMPs induce degradation of dermal proteins such as collagen, fibronectin and elastin, contributing to skin damage; therefore fucoidan may be useful to prevent skin photoaging not only by scavenging ROS formed during exposition to UV radiations, but also by inhibiting the formation of MMPs.…”
Section: Anti-pollution Ingredients From Algaementioning
confidence: 99%